Adaptation of the Friedman Life Balance Scale in Nursing Students into Turkish: Methodological (Validity and Reliability) Study. - TUNCER, Gülsüm Zekiye; YİGİT, Tülay Tuğçe; TUNCER, Metin (Turkiye Klinikleri Journal of Nursing Sciences, 2025)
Objective: The aim of this study is to adapt the Friedman Life Balance Scale (FLBS), originally developed in the USA, into Turkish and to examine its validity and reliability for assessing life balance among nursing students. Material and Methods: This methodological study was conducted with a sample of 688 nursing students enrolled in the faculty of nursing between November 2023-February 2024. The data were collected using the Satisfaction with Life Scale (SLS), the Warwick-Edinburgh Mental Well-Being Scale Short Form (WEMWBSF), and the FLBS. Initially developed in English, the 15-item scale comprising 3 sub-dimensions underwent Turkish language and content validity procedures. Results: The factor analysis results of the FLBS indicated that the construct validity was satisfactory. Exploratory factor analysis revealed a 3-factor structure accounting for 55.9% of the total variance. The goodness of fit values (χ²/df=3.516; Comparative Fit Index=0.953; Normed Fit Index=0.936; Incremental Fit Index=0.954; Tucker-Lewis Index (TLI)=0.931; Root Mean Square Error of Approximation= 0.060) of the model obtained with this 3-factor confirmatory factor analysis were good. The internal consistency Cronbach's alpha score of the FLBS was 0.861. In parallel form reliability of the FLBS, there was a low-level positive relationship between the FLBS and SLS (r=0.348, p<0.001) and a moderate positive relationship between the FLBS and WEMWBS (r=0.594, p<0.001). Conclusion: In this study, the Turkish version of the FLBS is a reliable and valid measurement tool for measuring life balance in nursing students. FLBS is a short and practical scale to measure life balance. It is thought that the FLBS can be used to measure life balance in students and health professionals.